2015
DOI: 10.1016/j.yebeh.2015.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species pharmacological characterization of the allylglycine seizure model in mice and larval zebrafish

Abstract: Treatment-resistant seizures affect about a third of patients suffering from epilepsy. To fulfill the need for new medications targeting treatment-resistant seizures, a number of rodent models offer the opportunity to assess a variety of potential treatment approaches. The use of such models, however, has proven to be timeconsuming and labor-intensive. In this study, we performed pharmacological characterization of the allylglycine (AG) seizure model, a simple in vivo model for which we demonstrated a high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 81 publications
3
23
0
2
Order By: Relevance
“…In this study, we observed that spontaneous epileptiformlike events in the form of abrupt high-voltage spikes, spikewave complexes, and polyspike-wave discharges occurred in 92% of cacna1aa morphants. Previous studies indicated that chemicals (e.g., pentylentetrazole or allylglycine) [37,39,53] as well as mutations in different genes (e.g., scn1lab, aldh7a1) [22,24] increase locomotor activity in zebrafish larvae reminiscent of tonic-clonic-like seizures. Indeed, tonic-clonic-like seizures have been described both in genetic and pharmacological models of epilepsy in zebrafish [22,54].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that spontaneous epileptiformlike events in the form of abrupt high-voltage spikes, spikewave complexes, and polyspike-wave discharges occurred in 92% of cacna1aa morphants. Previous studies indicated that chemicals (e.g., pentylentetrazole or allylglycine) [37,39,53] as well as mutations in different genes (e.g., scn1lab, aldh7a1) [22,24] increase locomotor activity in zebrafish larvae reminiscent of tonic-clonic-like seizures. Indeed, tonic-clonic-like seizures have been described both in genetic and pharmacological models of epilepsy in zebrafish [22,54].…”
Section: Discussionmentioning
confidence: 99%
“…compared AG-induced acute seizures in zebrafish larvae and adult mice. The results showed clear cross-species similarities with regard to seizure behavior and demonstrated limited efficacy of ASDs 13 . A drawback of the AG zebrafish model is that seizures occurred asynchronously and with a long latency to onset.…”
Section: Introductionmentioning
confidence: 95%
“…Besides ease of handling and fast reproduction rate, zebrafish share high genetic, cellular and organ homologies to humans 10 . Consequently, over recent years several chemical and genetic zebrafish models of acute seizures or epilepsy have been generated either by immersion of larvae in chemical proconvulsants like PTZ 11 , 12 or D-AG 13 , or by knocking down or introducing mutations in epilepsy susceptible genes including lgi1 14 , scn1Lab 15 , 16 , and kcnq3 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within just a few minutes of treating zebrafish larvae or adults with PTZ, epileptiform discharges and immediate-early gene expression are detectable in the brain, and accompanied by vigorous locomotor convulsive behaviours (Baraban et al, 2005;Mussulini et al, 2013;Afrikanova et al, 2013). PTZ has become the most widely used and extensively validated pharmacological inducer of acute seizures in zebrafish, but it is only one of a wide range of chemicals that have been shown to induce seizures and convulsions in zebrafish (Winter et al, 2008), and further studies have extended this range to include other well-characterized experimental convulsants which are known to be effective in mammals, such as Kainic Acid (Alfaro et al, 2011), its marine neurotoxin analogue Domoic Acid (Tiedeken and Ramsdell, 2007), the plant natural product ginkgotoxin (Lee et al, 2012) and Allyl-Glycine (Leclercq et al, 2015). Thus, many compounds that provoke seizures in mammals, do so with comparable efficacy in zebrafish.…”
Section: Recent Progress In Epilepsy Research Using Zebrafishmentioning
confidence: 99%